Investigation of partially expanded surge tank with self-adaptive auxiliary system controlling water hammer in pipelines - Wuyi Wan; Yuhang Wang; Xiaoyi Chen; Hang Zhan; Tiao Wang; Boran Zhang (Engineering Science and Technology, an International Journal, 2023)
Intensive water hammer can cause pipe collapse in long-distance water transfer pipeline systems. Pressure control facilities like surge tank have been widely applied to help control the extensive pressure fluctuations. In our previous work, a kind of spring self-adaptive auxiliary control (SAC) system was proposed and demonstrated to have a significant improvement on pressure control capacity of a normal surge tank. In this study, an additional solution, a partially expanded structural treatment, was introduced to a conventional SAC surge tank to further improve its functional ability. The 1D numerical model was established in our in-house codes on FORTRAN. The dominant geometrical parameters were identified and quantitatively studied with various cases. According to the effects of the geometrical parameters, a designing protocol for searching the optimal solutions of partially expanded SAC surge tank was concluded. With the obtained optimal solutions, the proposed partially expanded SAC surge tank can perform a much better pressure control performance dealing with valve closure induced water hammer, compared with a conventional SAC surge tank as well as a normal surge tank.